Identity-based student activism power and oppression on college campuses - Linder, Chris 1976-; Quaye, Stephen John 1980-; Lange, Alex C.; Evans, Meg E. (Routledge, 2020)
Historically and contemporarily, student activists have worked to address oppression on college and university campuses. This book explores the experiences of students engaged in identity-based activism today as it relates to racism, sexism, homophobia, transphobia, ableism, and other forms of oppression. Grounded by a national study on student activism and the authors' combined 40 years of experience working in higher education, Identity-Based Student Activism uses a critical, power-conscious lens to unpack the history of identity-based activism, relationships between activists and administrators, and student activism as labor. This book provides an opportunity for administrators, educators, faculty, and student activists to reflect on their current ideas and behaviors around activism and consider new ways for improving their relationships with each other, and ultimately, their campus climates
Keywords: Minority college students / Political activity / United States / Case studies; Student movements / United States / Case studies; Identity politics / United States / Case studies; Student-administrator relationships / United States / Case studies; Teacher-student relationships / United States / Case studies